Effect of Pulse Rate and Oxygen Saturation on the Duration of Wearing Mask among Nurses during the Pandemic of Coronavirus - aadi, hussein; Al-Jubouri, Mohammed Baqer Abbas; Al Omari, Omar (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The aim of this study is to determine the effect of pulse rate and oxygen saturation on the duration of wearing mask among nurses during the pandemic of coronavirus, and to find out the relationship between the duration of wearing mask and the nurse demographic characteristic of age, gender, level of education, and marital status. Methods: A quantitative descriptive study design was used in this study on 100 nurses worked at Wassit Province Hospitals at isolation units. A questionnaire used to collect the data of this study which consisted of two parts: (1) Sociodemographic characteristic of age, gender, level of education, marital status, Duration of wearying mask per time, and the type of mask they worn; and (2) Pulse oximetry to measure oxygen saturation and pulse rate. Data were analyzed by using SPSS version 23. Results: The results revealed that most of the study participant were males with mean age of 30.66 years old, and most of them have bachelors’ degree in nursing. All the study participants wear N95 face mask in which duration of wearing mask about 4.4 hours duration during working shift. Results also demonstrated that there were significant differences between the pulse rate and oxygen saturation before and after wearing masks at P=0.001, and a significant relation was presented between duration of wearing mask and oxygen level after wearing mask at P= 0.02. Conclusions: The study concluded that pulse rate has significant effect on the duration of wearing mask among nurses during the pandemic of COVID 19. Recommendations: The study recommends to minimize working shift time per day and limitation of the nurse movement at the isolation area except to necessary, so that to minimize their bodies’ oxygen consumption.